Characteristics of electricity production by metallic and nonmetallic anodes immersed in mud sediment using sediment microbial fuel cell. Issue 1 (September 2015) - Haque, N; Cho, D; Kwon, S
Abstract: Sediment microbial fuel cell (SMFC), equipped with Zn, Al, Cu, Fe or graphite felt (GF) anode and marine sediment, was performed. Graphite felt was used as a common cathode. SMFC was single chambered and did not use any redox mediator. The aim of this work was to find efficient anodic material. Oxidation reduction potential (ORP), cell voltage, current density, power density, pH and chemical oxygen demand (COD) were measured for SMFC's performance. The order of maximum power density was 913 mWm -2 for Zn, 646 mWm -2 for Fe, 387.8 mWm -2 for Cu, 266 mWm -2 for Al, and 127 mWm -2 for GF. The current density over voltage was found to be strongly correlated one another in most metal electrodes but the graphite felt electrode, in which relatively weaker electricity was observed because of its biooriented mechanism. Metal corrosion reactions and/or a complicated microbial electron transfer mechanism acting around the anodic compartment may facilitate to generate electricity. We presume that more sophisticated selection of anodic material can lead to better performance in SMFC.